Estimation of Stature of Adult Bangladeshi Male from the Length of the Foot - Parash, M Tanveer Hossain; Naushaba, Humaira; Paul, Uttam Kumar; Rahman, Md. Ashfaqur; Farhat, Nazma; E-Tabriz, Shams (Bangladesh Journal of Anatomy, 2013)
DOI: http://dx.doi.org/10.3329/bja.v9i2.15277 Bangladesh Journal of Anatomy 2011 Vol.9(2) pp.84-88